2019
DOI: 10.2478/jomb-2018-0045
|View full text |Cite
|
Sign up to set email alerts
|

Thiol-disulphide homeostasis in essential thrombocythemia patients

Abstract: Summary Background This study aimed to show the status of thioldisulphide homeostasis in essential thrombocytosis patients, which is known to play a role in platelet function. Methods The study included 27 ET patients and a control group of 36 healthy subjects. Serum total (–SH + –S–S–) and native (–SH) thiol levels were measured in all subjects using an automatic method. Results Age and gender distribution were similar in both groups. Compared with the control group, in the ET group, there were increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Typically, an increase in sulfhydryl content indicates alterations to a protein’s structure ( 37 ). Therefore, sulfhydryl and disulfide bond analysis were indispensable for evaluating the structural and functional changes in QA ( 38 ). As shown in Figure 2 , with increasing temperature, the content of sulfhydryl groups first increased and then decreased ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, an increase in sulfhydryl content indicates alterations to a protein’s structure ( 37 ). Therefore, sulfhydryl and disulfide bond analysis were indispensable for evaluating the structural and functional changes in QA ( 38 ). As shown in Figure 2 , with increasing temperature, the content of sulfhydryl groups first increased and then decreased ( P < 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Several studies found that FV Leiden and FII G20210A gene variants are major risk factor for recurrent miscarriage (34)(35)(36)(37)(38)(39)(40). Other studies, however found weak or no association of mentioned mutations and RPL (4,41,42).…”
Section: Discussionmentioning
confidence: 99%
“…As a result, dynamic thiol / disulfide homeostasis is achieved, and the organism is protected from the damage of reactive oxygen products. 10 This study investigated TAS, TOS, OSI, total thiol and native thiol levels and the quantity of dynamic disulfide bonds in acute ITP, chronic ITP and control groups, and the relationship between these components was investigated.…”
mentioning
confidence: 99%